Peran Citra Merek, Celebrity Endorser, Kualitas Produk Dalam Keputusan Pembelian - Anggi Tri Utami; Jeanne Ellyawati (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
Nowadays, almost everyone uses smartphones in their daily activities. This is an opportunity for the smartphone industry to produce good products and create consumer attractiveness so that consumers want to buy them. This study aims to determine the role of brand image, product quality, and celebrity endorser in purchase decisions. Data collection was gathered online via google form using a structured questionnaire. A total of 200 samples were recruited using a purposive sampling method. The sample used as respondents are consumers who have purchased a Vivo brand smartphone during last year. This study uses the SmartPLS statistical tool to process data. The results showed that brand image and product quality had a significant positive effect on purchase decisions. Meanwhile, celebrity endorser has no effect on the purchase decision.